PENJATUHAN HUKUMAN TERHADAP PELAKU TINDAK PIDANA TANPA HAK MEMBAWA DAN MEMILIKI SENJATA API (STUDI KASUS NOMOR, 83/PID.SUS/2018/PN.PSP) - Marwan Busyro; Bandaharo Saifuddin (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2020)
Crimes without the right to carry and possess a firearm (Case Study Number, 83/Pid.Sus/2018/PN.Psp). This study authors addressed the problem, namely, how is the judge's consideration in sentencing a criminal offender without the right to carry and possess a firearm based on the District Court's Verdict of Padangsidimpuan No., 83/Pid.Sus/2018/PN.Psp and how to apply the most punishment sentencing offenders without the right to carry and possess firearms based on the District Court's Verdict of Padangsidimpuan Number, 83/Pid.Sus/2018/PN.Psp? The research methods that the authors used in the writing of this study are qualitative and normative research that uses skunder data sources and in the form of legislation, as well as the District Court Of Padangsidimpuan Ruling that has the legal power to stick with this research is the research conducted with the results of the author's interview with the respondent and also conducts research on the data and files related to this research by conducting Field Research (Field Research) and Field Research (Field Research). The Judge's consideration in sentencing the perpetrators of crimes participated in storing the senajata fire and ammunition based on the District Court's Verdict padangsidimpuan Number, 83/Pid.Sus/2018/PN.Psp where the evidence tools namely witness statements and statements of the defendant accompanied by evidence submitted in the indictment letter by the Public Prosecutor. That the application of punishment against the perpetrator of a crime without the right to carry and possess a firearm based on the District Court's Verdict of Padangsidimpuan Number, 83/Pid.Sus/2018/PN.Psp is in accordance with what has been applied in the Law where the defendant is sentenced to a criminal conviction against the defendant therefore with a prison sentence of 1 (one) Year because the defendant admitted all his actions in the event of possessing without a license to carry a firearm